"My aunt unfriended me:" Narratives of GLBTQ Family Relationships Post 2016 Presidential Election. Issue 1 (15th March 2018) - Gonzalez, Kirsten A.; Pulice-Farrow, Lex; Galupo, M. Paz
ABSTRACT: This study focuses on the impact of the 2016 US presidential election on gay, lesbian, bisexual, transgender, and queer (GLBTQ) peoples' relationships with their family-of-origin. Although family relationships play an important role for all people, GLBTQ individuals' relationships with their families are particularly important during times of sociopolitical change, and when GLBTQ rights are being threatened. Specifically, the election of Donald J. Trump mandates a direct need to more thoroughly explore how the 2016 US presidential election has impacted GLBTQ individuals' relationships with their families. Participants included 274 individuals who identified as a part of the GLBTQ community, and completed an online survey in which they discussed the impact that the 2016 US presidential election had on their family-of-origin. Thematic analysis revealed three relationship-salient themes: (a) family divisions, (b) family cohesions, and (c) no change. Discussion of the results focuses on the critical role played by GLBTQ peoples' families during times when GLBTQ prejudice is politicized.